Exploring Zakat Payment Awareness and its Impact among MSMEs in Kartasura, Central Java, Indonesia - Alam, Azhar; Widiastuti, Tika; Faizah, Anisa Nur; Ashfahany, Afief El (ZISWAF, 2022)
This study aims to review the level of awareness of business zakat and its impact on business progress. The data for this research originated from the micro, small, and medium enterprises (MSME) business actors in Kartasura Subdistrict, Central Java, Indonesia. This study uses a qualitative approach to explore the awareness of business zakat and its impact on business progress. The open-ended interviews with a single case study from micro, small, and medium-sized enterprises (MSMEs) in the Kartasura sub-district, Central Java, Indonesia, were executed for data collection. 10 MSME businessmen were interviewed. The data was evaluated using the interpretative approach of the deductive method. The results showed the authors' deductive reasoning from the interview participants, explaining the informants' knowledge regarding zakat from commercial businesses and the impacts that might correspond to their business progress. This research underscores the importance of zakat awareness among MSME businessmen in Indonesia to further practice zakat in their businesses. This research recommended that MSME businesspeople need to know how to boost their zakat knowledge. MSME players must also include their staff to grasp their duties and the social purpose of zakat compliance, which will boost business development. Zakat management coordinators like BAZNAS must pay attention to MSMEs' compliance and zakat literacy because many sectors of the Indonesian economy still rely on them.